ANALISIS SIFAT FISIK DAN KIMIA PATI DARI TIGA VARIETAS SUKUN (Artocarpus sp.) - Syane Palijama; Josephina Talahatu; Izaac Joshua Huwae (Universitas Pattimura, 2017)
Breadfruit as an agricultural commodity with high carbohydrate content, can be functioned whether as a food reserve or as an alternative food resource. It also can improve diversity among food products and add value to the product as well, when it is being processed into starch. More ever, the process of making breadfruit into starch can reduce number of unused fruits as a result of bad fruit quality and rotten fruit. The starch can be used as a basic ingredient of various processed agricultural products. This research was aimed to analyze physical and chemical of starch contained in three breadfruit varieties. A completely randomized design was applied in this research with three levels of treatments, i.e.: ‘batu’ breadfruit starch (A1), ‘duri’ breadfruit starch (A2), and ‘kapas’ breadfruid starch (A3). Analyzed variables were water content, ash, amylase content, swelling power and solubility. Result indicated that ‘batu’ breadfruit starch had the highest value on variables of ash content, amylase content and solubility which were 0,09 percent, 19,67 percent and 24,07 percent respectively, while its water content and swelling power which were 3,74 percent and 17’37 g/g was the lowest value among other breadfruit starch. The highest water content and swelling power which were 6,64 percent and 20,01 g/g were found in ‘duri’ breadfruit starch. Keywords: breadfruit, starch, variety ABSTRAK Sukun (Artocarpus sp.) sebagai salah satu komoditas pertanian penghasil karbohidrat yang cukup tinggi dan berperan penting sebagai cadangan pangan ataupun sebagai bahan pangan alternatif. Pengolahan sukun menjadi pati dapat meningkatkan diversifikasi produk pangan dan dapat memberi nilai tambah dan mengangkat sukun menjadi komoditas yang bernilai tinggi. Selain itu, pengolahan sukun menjadi pati diharapkan dapat mengurangi jumlah sukun yang terbuang percuma karena rusak ataupun busuk, karena dapat berguna sebagai bahan utama olahan produk pertanian. Penelitian ini bertujuan untuk mengetahui sifat fisik dan kimia dari tiga varietas sukun. Rancangan yang digunakan adalah rancangan acak lengkap yaitu varietas sukun yang terdiri dari tiga perlakuan yaitu: A1 (Pati Sukun Batu), A2 (Pati Sukun Duri), dan A3 (Pati Sukun Kapas). Peubah yang diamati berupa kadar air, kadar abu, kadar amilosa, swelling power dan daya larut. Hasil penelitian ini menunjukkan bahwa; pati sukun batu (A1) memiliki kadar abu, kadar amilosa dan daya larut tertinggi masing-masing sebesar 0,09%, 19,67% dan 24,07% dan memiliki kadar air dan swelling power terendah masing-masing sebesar 3,74% dan 17,37 g/g. Pati sukun duri (A2) memiliki nilai kadaar air dan swelling power tertinggi masing-masing sebesar 6,64% dan 20,01 g/g. Kata kunci: pati, sukun, varietas